Building Healthy Child Leaders Training E-Module: Training Materials for Mentors - Triwiyanto, Wahyudi; Iriani, Ade (Universitas Pendidikan Ganesha, 2022)
Building Healthy Child Leaders requires adults to act as mentors. The problem was the lack of materials and training for mentors. This research was intended to design, validate, create and implement a Building Healthy Child Leaders training e-module for mentors. The type of research used was R&D (research and development) by combining the Sugiyono, ADDIE and Kirkpatrick evaluation models. Research subjects for: 1) the initial stage were managers, mentors and FC coordinators; 2) the limited trial was STAK students; and 3) user trial was PESAT Foundation FC mentors. Quantitative data was obtained through questionnaires and tests, while qualitative data was obtained from interviews, observation and documentation. Qualitative data were analyzed by Miles & Huberman. Quantitative data were analyzed by descriptive statistical analysis. The results of the research were an Healthy Child Leaders training e-module product that met the Very Valid criteria (> 80%) from 3 expert validators; training participants' responses to the quality of the e-module was “Very Good” (>80); response to the implementation of the training was “Very Effective” (>80%); and inferential statistical analysis with Paired T Test showed sig. (2-tailed) of 0.000 < a(0.05), meaning that the e-module had a significant effect before and after training. So, the Healthy Child Leaders training e-module that was created met the criteria of Very Valid and Highly Effective to be used to train mentors. The implication is that mentors have the foundation, skills and opportunities for independent learning to build healthy child leaders.